Supervision of Madrasah Principal in Motivating Madrasah Aliyah Negeri's Performance in Jambi Province - Nurzila, Nurzila; Muntholib, Muntholib; Badarusyamsi, Badarusyamsi (Yayasan Sembilan Pemuda Indonesia, 2022)
The purpose of this research is to ascertain the role of principal supervision in motivating the performance of Madrasah Aliyah Negeri (MAN) 2 Tebo teachers in Jambi Province. This study employs a descriptive qualitative method with a case study approach, as well as data collection techniques such as observation, interviews, and documentation. The research is being conducted at MAN 2 Tebo in Jambi Province. The subjects of the study included the madrasah principal, deputy head, teaching staff, education staff, and students. The findings revealed that implementing principal supervision in stages, such as planning, implementation, and evaluation (reflection and self-assessment), had a positive impact on the motivation and performance of MAN teachers in Jambi Province. The research recommends that the Ministry of Religion of the Republic of Indonesia improve and even out its mapping in implementing the Education and Training program to improve the supervisory competence of madrasah principals at the Madrasah Aliyah level, so that improving the quality of education is evenly distributed throughout Madrasah in Indonesia.